Climate change and hunter-gatherers in montane eastern DR Congo. (28th May 2022) - Batumike, Rodrigue; Bulonvu, Franklin; Imani, Gérard; Akonkwa, Desiré; Gahigi, Aimable; Klein, Julia A.; Marchant, Rob; Cuni-Sanchez, Aida
ABSTRACT: Mountain environments experience more rapid changes in temperature than lower elevations. However, little is known about the climatic changes already observed in African mountains, or the adaptation strategies used by hunter-gatherer communities. Semi-structured interviews were administered to 100 Twa hunter-gatherers living around Mt Kahuzi in eastern Democratic Republic of the Congo (DR Congo). We also organized 10 focus-group discussions with Tembo farmers living in the same area and we gathered historical data from Kamembe meteorological station. Twa respondents perceived reduced rainfall and fog, and increased temperatures. They also reported several impacts including reduced crop yields and abundance of forest products (caterpillars, mushrooms, honey). Tembo perceptions of climatic changes and impacts agreed with the Twa. Meteorological data available shows reduced rainfall and increased temperatures – but there are no records on fog. Despite being aware of climatic changes and impacts, Twa are not using any adaptation strategy, while Tembo farmers are using some (as they own land for farming or animal rearing, and are more business minded). For the Twa, their socioeconomic condition create high sensitivity to climate change and constrain adaptive capacity. For the Twa, we recommend the use of 'science with society' (SWS) participatory approach.